A new multiple ant colonies optimization algorithm utilizing average pheromone evaluation mechanism - Aljanaby, Alaa; Ku-Mahamud, Ku Ruhana; Md Norwawi, Norita (2008)
Multiple ant colonies optimization is an extension of the Ant Colony Optimization framework It offers a good opportunity to improve the ant colony optimization algorithms by encouraging the exploration of a wide area of the search space without losing the chance of exploiting the history of the search.This paper proposes a new multiple ant colonies optimization algorithm that is based on ant colony system and utilizes ave rage pheromone evaluation mechanism.The new algorithm divides the ants’ populations into multiple ant colonies and can be used to tackle large volume combinatorial optimization problems effectively. Computational tests show promises of the new algorithm.